Revision of Codonoboea Sect. Boeopsis and sect. Salicini (Gesneriaceae) in Peninsular Malaysia / Lim Chung Lu - Lim, Chung Lu (2014)

(untitled)
Peninsular Malaysia is the centre of diversity of the genus Codonoboea Ridl. with 74 species recorded. In this study, species from sect. Boeopsis (11 spp.) and sect. Salicini (4 spp.) are studied. There are four objectives in this study, namely to provide detailed descriptions of species and a key to species of both sect. Boeopsis and sect. Salicini. Secondly, to produce distribution maps and assess conservation status of the species. Then thirdly, to determine whether all species with pollen flowers in Codonoboea are monophyletic using morphology and molecular phylogenetic data. And fourth and lastly, to determine the trend of evolution of the pollen flower from the nectar flower in Codonoboea. In this study, 15 species, including a new species, Codonoboea oreophila, are recognised. A key to all species is prepared for species identification. Detailed species description, nomenclature, geographical distribution, habitat and ecology of the species are provided, as well as a full list of specimens examined. Both sections were grouped due to the short corolla tube and other characters, i.e. rosette habit in sect. Boeopsis and narrow leaves in sect. Salicini. There are seven corolla shapes among the species. Informative morphological characters, such as corolla shape and colour, stamens and anther shape, are found to be useful for species identification. Molecular phylogenetic study based on trnL-F intron spacer and Internal Transcribed Spacer (ITS) markers was carried out using two Boea and four Microchirita species as outgroup and 38 samples of Codonoboea (14 from species in this study) as ingroup. The data are analysed using Bayesian Inference and Maximum Parsimony methods. iv Fourteen of the 15 species are endemic in Peninsular Malaysia. Most species are found on the east coast of Peninsular Malaysia, which is determined as the centre of species diversity. Five species fall within threatened categories when conservation status for all species was assessed. To answer the trend of pollen and nectar flower evolution in Codonoboea, morphological characters were mapped on molecular phylogenetic trees. The result showed conclusively that both Boeopsis and Salicini sections are not monophyletic and morphological characters of Codonoboea are very plastic. The evolution of corolla shapes could be due to adaptation to pollinator, which is Trigona bees.